Rest in underperforming elite competitors. Issue 4 (December 1990) - Koutedakis, Y; Budgett, R; Faulmann, L
Abstract : This study examines the effects of 3-5 weeks of physical rest on selected physical, physiological and psychological parameters obtained from 12 Olympic but latterly underperforming competitors and their matched control subjects. Cardiorespiratory data were directly determined from their work to volitional exhaustion on either a treadmill, cycle, or rowing ergometer. Anaerobic power and capacity were evaluated through modified Wingate tests. For psychometric assessments, the Profile of Mood States (POMS) was used. For the Olympic competitors, one-way analyses of variance (ANOVA) revealed significant increases (p less than 0.05) in body weight, maximum respiratory exchange ratio, maximum oxygen consumption, and heart rate at the anaerobic threshold, following the rest period. There was also a significant reduction in fatigue and mood profile score, and a significant increase in vigour. No significant changes were found in the matched control subjects. The present data show that resting for 3-5 weeks assists underperforming elite competitors to improve their aerobic performance.